Makna Simbol Dalam Interior Gereja Katolik Santo Yusuf Gedangan Semarang - Clarissa Nathania; Purnama Esa Dora Tedjokoesomo (Intra, 2015)
St.Joseph’s Catholic Church Gedangan is the forerunner of the Catholic Church in Indonesia. This church is a relic of the Dutch colonial era, so it has historical value and unique both in terms of architecture and interior elements. In the interior elements of this church there is are synbols that are used. These symbols not only as form of aesthetics only, but has special meaning to be conveyed by the symbols on each part. To get the meanings embodied in symbols in this church, researchers used the basic theory of meaning by Roland Barthes. There are two meanings, which are denotation meaning and connotative meaning. Denotation meaning produces a discrption of an existing symbol, while conotative meaning generate meaning contained within symbol. The result showed that in each symbol with different placement have different meanings, and each symbol that is an expression of the faith of Catholic.